Optimasi Memaksimumkan Keuntungan Produksi Pada Bulu Mata PT. Daux Cosmetic Menggunakan Linear Programming - Muhamad Fahmi Nugraha; Nerva Auliana Putriyanti; Anjas Tryana; Tedi Budiman (Masoem University, 2026)
PT. Daux Cosmetic, an eyelash manufacturer located in Garut, Indonesia, faces challenges in optimizing the production mix of two eyelash models—Model A and Model B—under limited production and quality control time. This study aims to determine the optimal production combination to maximize profit using Linear Programming (LP). Two complementary approaches were employed: the graphical method for feasible-region visualization and the simplex method for iterative algebraic solution. Based on the LP formulation with objective function Z = 10,000,000X? + 4,500,000X? and two capacity constraints, the optimal solution was obtained at point B (X? = 10, X? = 60), allocating 10 hours to Model A and 60 hours to Model B, yielding a maximum profit of IDR 370,000,000. Both methods yielded consistent results, confirming LP as a reliable production-planning tool and a sound basis for operational decision-making.